PENDUGAAN POTENSI SUMBERDAYA PERIKANAN LAUT DAN TINGKAT KERAGAAN EKONOMI PENANGKAPAN IKAN (KASUS DI TPI SENDANG BIRU KABUPATEN MALANG) - Hulaifi Hulaifi (LPPM Universitas Terbuka, 2011)
The Increased fishing intensity will provide positive and negative impacts. Positive impact is an increase in production that can provide benefits, while the negative impact is eventually decline in production catches. The purpose of this research is potential of Estimating Maximum Sustainable Yield (MSY) in Malang Regency could still be maintained. MSY at the level of Maximum Economic Yield (MEY). Optimization of fishing effort and analysis economic eligibility fishing effort. The method of research using the survey method, Analysis of the data used is static Bio-economic model, and Gorden-Schaefer model. While the research results obtained MEY value of 5,789,952. kg/year and the actual conditions, a production of 5,221,781 kg/year and MSY of 5,829,206 kg/year, the rate of 90% utilization optimization, and optimal fishing levels have exceeded MSY. The advantage of fishermen in biology and economics as much as 5,789,952 kg/year. Conclusion The results showed that the water condition in Malang Regency was not economically efficient, because already there is excess fishing effort. Optimization needs to be done by limiting fishing effort, intensified fishing activities in deeper waters.